2018
DOI: 10.1111/josi.12255
|View full text |Cite
|
Sign up to set email alerts
|

Deviance Credit: Tolerance of Deviant Ingroup Leaders is Mediated by Their Accrual of Prototypicality and Conferral of Their Right to Be Supported

Abstract: Leaders often deviate from group norms or social conventions, sometimes innovating and sometimes engaging in serious transgressions or illegality. We propose that group members are prone to be more permissive toward both forms of deviance in the case of ingroup leaders compared to other ingroup members or outgroup members and leaders. This granting of “deviance credit” is hypothesized to be underpinned by perceptions of an ingroup leader's prototypicality of the group (“accrual”) and belief that occupancy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 40 publications
3
50
1
1
Order By: Relevance
“…Often prototypical leaders hold an advantage both in attaining leadership and changing and defining group norms (Reicher & Hopkins, ). The prototypical leader advantage extends to people allowing their prototypical leaders to both commit transgressions and change group norms (Abrams et al., ). Yet, we also present caveats to the prototypical leader advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often prototypical leaders hold an advantage both in attaining leadership and changing and defining group norms (Reicher & Hopkins, ). The prototypical leader advantage extends to people allowing their prototypical leaders to both commit transgressions and change group norms (Abrams et al., ). Yet, we also present caveats to the prototypical leader advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Abrams, Randsley de Moura, and Travaglino () found that sports team members evaluate ingroup team captains (leaders) who break the rules more favorably than others who commit the same transgressions. Group members trust prototypical leaders to act in their best interest and, as a result, view a leader who transgresses as doing so in service of the group (see also Abrams, Travaglino, Randsley de Moura, Pinto, & Levine, ). Shapiro, Boss, Salas, Tangirala, and Von Glinow () found that employees judged transgressing leaders less harshly to the extent that they found their leaders capable and inspirational, lending support to the idea that group members provide leaders leeway to transgress, even if the morality of the action would be scrutinized had others perpetrated it.…”
Section: Leading Changementioning
confidence: 99%
“…Brauer and Chekroun, 2005;Chekroun, 2008), but communicating disapproval directly to the leader may not be feasible, particularly if the group is very large. Previous research has established that ingroup leaders are often given latitude to deviate from group norms (Abrams et al, 2018). Ingroup leaders who commit unethical actions are less likely to be derogated or punished than other ingroup members or outgroup leaders and members who commit the same transgressive actions; a phenomenon labeled 'transgression credit' (Abrams et al, 2013;Randsley de Moura and Abrams, 2013).…”
Section: Ethical and Unethical Leadershipmentioning
confidence: 99%
“…Demonstrations of “being one of us” and “understanding how things are done around here” earn an individual the ability to deviate while maintaining credibility in the eyes of other group members. Evidence suggests that higher status group members are often afforded more latitude for deviance (Abrams et al., ; Abrams, Travaglino, Marques, Pinto, & Levine, ). We further hypothesize—and this is the crux of the current argument—that normativity and prototypicality are not entirely defined by opinions or behavior (what a person thinks or does; i.e., variety diversity), but also what they look like and their social category memberships (i.e., disparity diversity).…”
Section: Reactions To Influence Attempts: Prototypicality Rulesmentioning
confidence: 99%